The resilience of the military leader – defining traits and its ability to influence the operational environment - Marius Iulian BADIU; Laura-Alexandra ȚICĂ (Bulletin of "Carol I" National Defense University, 2023)
The military environment, by its very nature, is recognized as a source of occupational stress. The military’s approach to measuring stressors, analyzing and comparing them with the capacity to cope, gives rise to both distress and eustress. Challenges arise when the effects of stress surpass an individual’s ability to adapt, hindering their response to new demands. Military organizations highly value resilience as the key to effectiveness and success. In the military context, resilience can be viewed as a process, skill, or outcome, wherein military leaders exhibit the ability to confront fear, navigate outside their comfort zone, and overcome challenging moments in pursuit of a greater purpose